The political economy of reform : lessons from pensions, product markets and labour markets in ten OECD countries - Tompson, William; Price, Robert (Paris : Organisation for Economic Co-operation and Development, 2009)
This report examines why some policy reforms get implemented and others languish by examining 20 structural reform efforts in 10 OECD countries over the past two decades. The case studies cover a wide variety of reform attempts in three key areas: pensions, labour- and product-market regulation. Key factors in the political, economic and reform-specific arenas are identified as helping or hindering reform, and these findings are cross-checked using a relatively simple set of Spearman rank correlations. The report’s two-pronged analytical approach – quantitative and qualitative – results in unique insights for policy makers designing, adopting and implementing structural policy reforms
Obsahuje bibliografické odkazy
Keywords: strukturální politika; hospodářská politika; důchodové reformy; služby; trh práce; země OECD; studie; structural adjustment; economic policy; pension reforms; service industries; labor market; OECD countries; studies